Conocimiento y responsabilidades del trabajador independiente del bajo Ricaurte en el Departamento de Boyacá frente a la UGPP (2021)
The main purpose of the following work is to analyze the role of the Pension and Parafiscal Management Unit (UGPP), as a supervisory entity and its importance for companies.